Implikasi Other Comprehensive Income IFRS pada Perpajakan Indonesia - Prianto Budi Saptono; Ismail Khozen (Universitas Winaya Mukti, 2022)
In Indonesia, the Statement of Financial Accounting Standards (PSAK) 1 does have guidelines about Other Comprehensive Income (OCI). Tax issues usually arise when an entity seeks to reconcile any type of OCI with the definition of income under Income Tax Law Article 4 paragraph (1). This research aims to analyze the implication of OCI on the income tax environment in Indonesia. This study use a qualitative methodology with the data mainly acquired from literature and in-depth interviews. To guarantee that the principle of ability to pay is upheld, each components of OCI demand separate treatments. According to the findings, Indonesian income tax regulations on OCI components could be based on realization, mark-to-market, or a hybrid of these approaches. Gains and losses from financial statement translation of international business activity might be taxed through realization taxation. Hybrid taxation better serve the unrealized gains and losses of fixed assets and intangible asset changes in revaluation surplus. It is preferable to use the mark-to-market approach if the tax authorities has given its consent for the revaluation to be carried out. Realization taxation should be imposed on the remaining components as well. Some policy recommendations, as a result of our findings, for the development of future tax policies are highly encouraged.